Doing Business in 2006 : Creating Jobs - World Bank (Doing Business, 2005)
Doing Business in 2006 is the third in a series of annual reports investigating regulations that enhance business activity and those that constrain it. This edition provides analysis on those regulations that help create jobs and those that deter it. New quantitative indicators on business regulations and their enforcement can be compared across 150 countries - from Albania to Zimbabwe - and over time. Doing Business in 2006 updates the indicators presented in previous reports: on starting a business, hiring and firing workers, getting licenses, getting credit, protecting investors, enforcing contracts, and closing a business. Two news sets of measures are added, on paying taxes and trading across borders. The indicators are used to analyze economic and social outcomes, such as productivity, investment, informality, corruption, unemployment and poverty, and identify what reforms have worked, where and why